Kidney and heart failure events are bidirectionally associated in patients with type 2 diabetes and cardiovascular disease - Abhinav Sharma; Silvio E. Inzucchi; Jeffrey M. Testani; Anne Pernille Ofstad; David Fitchett; Michaela Mattheus; Subodh Verma; Faiez Zannad; Christoph Wanner; Bettina J. Kraus (ESC Heart Failure, 2024)
Abstract Aims This study aimed to evaluate the bidirectional relationship between kidney and cardiovascular (CV) events in trial participants with type 2 diabetes and CV disease. Methods and results Post hoc analyses of EMPA‐REG OUTCOME using Cox regression models were performed to assess the association of baseline factors with risk of a kidney event and bidirectional associations of incident kidney events and CV events. Among placebo‐treated participants, baseline factors significantly associated with greater kidney event risk included lower baseline estimated glomerular filtration rate, albuminuria, higher uric acid, low‐density lipoprotein cholesterol levels, and prior heart failure (HF). Coronary artery disease was not associated with increased risk. In placebo‐treated participants, occurrence of an incident non‐fatal kidney event increased the subsequent risk of hospitalization for HF (HHF) but not 3‐point major adverse CV events (non‐fatal stroke, non‐fatal myocardial infarction, and CV death). Vice versa, HHF (but not myocardial infarction/stroke) increased the risk of subsequent kidney events. These associations were generally also seen in empagliflozin‐treated participants and in the overall population. Interestingly, the risk of kidney events following HHF was not significantly increased in the relatively small number of placebo‐treated participants already diagnosed with HF at baseline. Conclusions These findings demonstrate a bidirectional inter‐relationship between HHF and kidney events. Further exploration of this relationship and strategies to optimize the use of therapies to reduce both kidney and HF outcomes is warranted.